Myeloma cell-derived CXCL7 facilitates proliferation of tumor cells and occurrence of osteolytic lesions through JAK/STAT3 pathway - Yue Wang; Tianwei Lan; Qiongyan Zhang; Chi Zhou; Peng Liu (Cell Death and Disease)
Abstract Osteolytic lesions and pathological fractures are hallmark manifestations of multiple myeloma (MM), profoundly influencing the quality of life and self-care ability of MM patients. By analyzing transcriptome data and single-cell RNA-seq data from our center and the GEO database, a subset of MM cells with high expression levels of chemokine CXCL7 was identified. This subset of MM cells possesses a high capacity for proliferation and activation of osteoclast signaling pathway. CXCL7 might be a crucial regulator of osteolytic damage in MM. Subsequently, the association between the expression level of CXCL7 and pathological fractures in patients was investigated, and the impact of CXCL7 on MM proliferation was confirmed both in vivo and in vitro. A mouse xenograft tumor model was established through intravenous injection of myeloma cell lines based on the homing ability of plasma cells. Moreover, the mechanism by which CXCL7 promotes the activation of osteoclast signaling pathways in MM was explored. Our findings reveal that elevated CXCL7 levels significantly enhance MM cell proliferation, increasing the risk of pathological fractures in MM patients. Additionally, our mouse xenograft tumor model demonstrated that CXCL7 can induce femoral fractures and reduce bone mineral density. Concurrently, it was discovered that CXCL7 could activate the JAK/STAT3 pathway via CXCR2 and upregulate the expression levels of MMP13 and C-myc, facilitating MM cell proliferation and activation of the osteoclast signaling pathway. Our study offers novel insights into the pathogenic mechanism of osteolytic lesions and implies that targeting CXCL7 may present a new therapeutic avenue for MM.